Advanced Medieval Historiography in Central Asia (Pedagogical Cluster-Journal of Pedagogical Developments, 2024)
One of the largest states formed in the former territory of the Baghdad Caliphate was the Samanid state (819-999 AD). By the end of the 10th century, feudal disunity intensified. In Hamadan, Isfahan and Rai, the Buwahys, and in Tabaristan and Jurjan, the Ziyaris gained independence. In 962, Alptakin, the deputy of the Somonites in Ghazni, also declared independence. The lands on the right bank of the Syrdarya, as well as Chaganiyan and Khorezm, refused to obey the Somanites. The study of the historiography of the state of the Khorezmshahs, especially after the establishment of the Independent Republic of Uzbekistan, was revived. The services of Azamat Ziya, Azod Masharipov, Matyakub Maniyozov, Abdulla Sotlikov, Anatoly Sagdullaev and others were effective in this field.